Mujahadah Asmaul Husna Terhadap Spiritualitas Jama’ah: Analisis Fenomenologi Agama pada Jama’ah Mushola Al-Furqon Sumpiuh Banyumas - Nuraziz, Sigit Candra; Mawardi, Khalid (Al-Wasathiyah: Journal of Islamic Studies, 2024)
This research is intended to explore the concept of a phenomenological approach to the spirituality of the congregation in Mujahadah Asmaul Khusna activities, where the congregation will regularly feel the beneficial impact for those who are steadfast in carrying it out. The method used in this research uses qualitative research methods, with a qualitative descriptive phenomenological approach, as well as data collection techniques carried out in the form of interviews, observation and documentation to support the entire research process. Recently, the problem experienced by humans is the lack of spiritual intake within themselves as a form of strengthening their fortress in self-defense against things that can harm themselves. In fact, the spirit in humans can be compared to a battery, which can run out at any time, so we need to replenish our spiritual needs, one of which is by means of Mujahadah Asmaul khusna. The results of this research show that the experiences of the Asmaul Khusna Mujahadah congregation are very diverse and this becomes a spiritual experience for the congregation after practicing it regularly and consistently. The experience experienced is abstract in nature and cannot be described clearly by the author, but it can be seen in changes in behavior and actions that are more focused and wise, to achieve social piety and an increase in the personal religiosity of a congregation of the Mujahadah Asmaul Khusna. If Mujahadah activities are felt to be beneficial then this or the spiritual experience experienced by the congregation is felt to be true because it can show different behavior in their way of life.